Motor associations of iron accumulation in deep grey matter nuclei in Parkinson's disease: a cross‐sectional study of iron‐related magnetic resonance imaging susceptibility. (16th December 2016) - Martin‐Bastida, A.; Lao‐Kaim, N. P.; Loane, C.; Politis, M.; Roussakis, A. A.; Valle‐Guzman, N.; Kefalopoulou, Z.; Paul‐Visse, G.; Widner, H.; Xing, Y.; Schwarz, S. T.; Auer, D. P.; et al.
Abstract : Background and purpose: To determine whether iron deposition in deep brain nuclei assessed using high‐pass filtered phase imaging plays a role in motor disease severity in Parkinson's disease (PD). Methods: Seventy patients with mild to moderate PD and 20 age‐ and gender‐matched healthy volunteers (HVs) underwent susceptibility‐weighted imaging on a 3 T magnetic resonance imaging scanner. Phase shifts (radians) in deep brain nuclei were derived from high‐pass filtered phase images and compared between groups. Analysis of clinical laterality and correlations with motor severity (Unified Parkinson's Disease Rating Scale, Part III, UPDRS‐III) were performed. Phase shifts (in radians) were compared between HVs and three PD subgroups divided according to UPDRS‐III scores using analysis of covariance, adjusting for age and regional area. Results: Parkinson's disease patients had significantly ( P < 0.001) higher radians than HVs bilaterally in the putamen, globus pallidus and substantia nigra (SN). The SN contralateral to the most affected side showed higher radians ( P < 0.001) compared to the less affected side. SN radians positively correlated with UPDRS‐III and bradykinesia−rigidity subscores, but not with tremor subscores.ancova followed by post hoc Bonferroni‐adjusted pairwise comparisons revealed that SN radians were significantly greater in the PD subgroup with higher UPDRS‐III scores compared to both lowest UPDRS‐III PD and HV groups ( P < 0.001). Conclusions: Increased nigral iron accumulation in PD appears to be stratified according to disease motor severity and correlates with symptoms related to dopaminergic neurodegeneration. This semi‐quantitative in vivo iron assessment could prove useful for objectively monitoring PD progression, especially in clinical trials concerning iron chelation therapies.